New Insights Into Metabolic Syndrome - Takada, Akikazu (IntechOpen, 2021)
Contributors to this book have reviewed research from the fields of metabolic syndromes in view of their own research. The chapters cover the neural mechanisms of food intake and proposed factors related to obesity. The influences of the intake of sugar and lipids are also discussed. The relationships between cancer and venous thromboembolism in connection with obesity are discussed. Omega (ω) fatty acids and trans-fatty acids are risks of cardiovascular diseases. Comparison of plasma levels of trans-fatty acids indicated that industrially produced trans-fatty acids are higher in American than Japanese men. Hopefully, the book provides information that readers want to obtain in the fields of food intake and metabolic syndromes.